The Influence of Personal Selling and Digital Marketing on the Sales Performance of Laboratory Service Through Customer Buying Interest at PT. Prodia in Makassar City - Hermin Tikumaqdika, Sumardi, Muh. Thoaha (STIE Amkop Makassar, 2023)
The aim of this study is to determine and analyze the influence of personal selling and digital marketing on the sales performance of laboratory services through customer buying interest at PT. Prodia in Makassar City. The research methodology used descriptive method and path analysis technique for data collection through observation and questionnaires. The results of the study indicate that personal selling and digital marketing have a positive and significant impact on customer buying interest. Personal selling and digital marketing also have a positive and significant influence on the sales performance of laboratory services at PT. Prodia in Makassar City. Customer buying interest has a positive and significant impact on the sales performance of laboratory services. Furthermore, based on the results of the online Sobel test, it can be concluded that customer buying interest mediates the influence of personal selling and digital marketing on the sales performance of laboratory services at PT. Prodia in Makassar City.